2011
DOI: 10.1039/c1cp21061k
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing carbon-lithium stars

Abstract: We have explored in silico the potential energy surfaces of the C(5)Li(n)(n-6) (n = 5, 6, and 7) clusters using the Gradient Embedded Genetic Algorithm (GEGA) and other computational strategies. The most stable forms of C(5)Li(5)(-) and C(5)Li(6) are two carbon chains linked by two lithium atoms in a persistent seven membered ring capped by two Li atoms. The other Li atoms are arrayed on the edge of the seven membered ring. In contrast, the global minimum structure for C(5)Li(7)(+) is a bicapped star of D(5h) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…The minimum energy conformation of the last explored system, Li 7 (BH) 5 + , was manifested as a highly symmetric starshaped structure (D 5h , 3), consisting of a (BH) 5 pentagon surrounded by seven lithiums. This system is structurally similar to the Li 7 Si 5 + (D 5h ) 20 and Li 7 C 5 + (D 5h ) 25 clusters. The next higher-energy isomer contains the same (BH) 5 Please do not adjust margins Please do not adjust margins kcal/mol higher in energy when compared to the most stable one.…”
Section: Structural Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…The minimum energy conformation of the last explored system, Li 7 (BH) 5 + , was manifested as a highly symmetric starshaped structure (D 5h , 3), consisting of a (BH) 5 pentagon surrounded by seven lithiums. This system is structurally similar to the Li 7 Si 5 + (D 5h ) 20 and Li 7 C 5 + (D 5h ) 25 clusters. The next higher-energy isomer contains the same (BH) 5 Please do not adjust margins Please do not adjust margins kcal/mol higher in energy when compared to the most stable one.…”
Section: Structural Analysismentioning
confidence: 69%
“…In previous works, the magnetic response of Li 7 Si 5 + and Li 7 C 5 + was reported. 20,25 Highly diatropic responses on those systems were identified by the induced magnetic field profiles. In the present work, a similar analysis was done for C 5 H 5 -(D 5h ), C 4 H 4 (D 2h ), C 5 H 5 + (C 2v ), Li 7 C 5 + (D 5h ), Li 7 Si 5 + (D 5h ), and Li 7 (BH) 5 + (D 5h ).…”
Section: Bonding Analysismentioning
confidence: 99%
“…Clusters with the formula Si 5 Li n n −6 ( n =5–7) are of particular interest to us because of their strong aromatic character, and when n =7, the lowest energy form is a beautiful starlike structure3d (see also the related paper of Perez‐Peralta and Boldyrev) 3e. More recently, we showed that the most stable configuration for C 5 Li 7 + is a D 5 h seven‐pointed star 4. Structures of Si 5 Li 7 + and C 5 Li 7 + can be described conceptually as ionic interactions of a flat E 5 6− pentagonal ring with seven satellite lithium cations.…”
Section: Introductionmentioning
confidence: 98%
“…This functional has been widely used for the calculation of magnetic properties in organic, inorganic and solid compounds, providing results comparable with experiments. 38,[54][55][56] Vibrational frequency calculations were performed at the same level to effectively obtain a true-minimum on the potential energy surface (PES), with the exception of the planar COT, which has one imaginary frequency (156.1i cm…”
Section: Computational Detailsmentioning
confidence: 99%